ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN MINAT BELI KONSUMEN DIBEDAR RESTO DAN KAFE DALAM PERSFEKTIF EKONOMI ISLAM - Asmarani; Budi Iswanto; Zulkan (Cross-Border Journal of Business Management, 2023)
This study aims to find out how to analyze marketing strategies in increasing consumer buying interest at Bedar Resto and Café in an Islamic economic perspective. This study used a qualitative approach and a type of field research. Data collection techniques were carried out through observation, interviews and documentation based on primary sources in the field and secondary sources in the form of books or research works related to this research. Based on the results of the study concluded that the quality of service, promotion, price, physical appearance, and process are prioritized in increasing consumer buying interest. As for the Islamic economic perspective, it has implemented the professionalism of the Prophet Muhammad, namely Shiddiq, Amanah, Fhatanah, and Tabliqh which have been practiced or implemented by business owners and Bedar Resto and Café employees managed by Mrs. Rina.